2011
DOI: 10.1074/jbc.m111.224964
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Transactivation Function and Stability of Krüppel-like Zinc Finger Protein Gli-similar 3 (Glis3) by Suppressor of Fused

Abstract: Glis3 is a member of the Glis subfamily of Krüppel-like zinc finger transcription factors. Recently, Glis3 has been linked to both type I and type II diabetes and shown to positively regulate insulin gene expression. In this study, we have identified a region within the N terminus of Glis3 that shares high levels of homology with the Cubitus interruptus (Ci)/Gli family of proteins. We demonstrated that Glis3 interacts with Suppressor of Fused (SUFU), which involves a VYGHF motif located within this conserved r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 49 publications
(72 reference statements)
0
41
0
Order By: Relevance
“…Several kinase pathways activated by TSH/TSHR have been implicated in mediating the downstream effects of TSH on gene expression, proliferation, and TH biosynthesis. We previously reported that GLIS3 undergoes a number of posttranslational modifications, including phosphorylation and ubiquitination, that can regulate GLIS3 transcriptional activity (54,55). This raised the possibility of a connection between TSH/TSHR-activated kinase pathways and the regulation of GLIS3 activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several kinase pathways activated by TSH/TSHR have been implicated in mediating the downstream effects of TSH on gene expression, proliferation, and TH biosynthesis. We previously reported that GLIS3 undergoes a number of posttranslational modifications, including phosphorylation and ubiquitination, that can regulate GLIS3 transcriptional activity (54,55). This raised the possibility of a connection between TSH/TSHR-activated kinase pathways and the regulation of GLIS3 activity.…”
Section: Discussionmentioning
confidence: 99%
“…The expression vectors p-3′FLAG-CMV-Glis3-HA, p-3′FLAG-CMV-Glis3ΔN496-HA, p-3′FLAG-CMV-Glis3ΔC480-HA, and pCMV-SUFU-Myc were described previously (54,55). pcDNA3.1-Pax8 was obtained from GenScript, and pcDNA3.1-TTF1 was a gift from David Mu (Pennsylvania State University, Hershey, PA, USA) (Addgene plasmid, catalog 49989).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, co-immunoprecipitation assay confirmed that the SUFU was able to interact with GLIS3 through the conserved VYGHF motif at N-terminus of GLIS3. Functional study showed that the SUFU repressed the activation of the insulin promoter mediated by GLIS3 (ZeRuth et al 2011). In addition, the E3 ubiquitin ligase scaffolding protein Cullin 3 (CUL3) promotes GLIS3 polyubiquitination and degradation via the 26S proteasomal pathway.…”
Section: Interacting Partners Of Glis3mentioning
confidence: 99%
“…SUFU was shown to inhibit the association of CUL3 with GLIS3, thereby protecting GLIS3 protein from proteolytic degradation and enhancing the stability of GLIS3 protein (Fig. 1A) (ZeRuth et al 2011).…”
Section: Interacting Partners Of Glis3mentioning
confidence: 99%
“…The ZFDs of GLIS1 and GLIS3 exhibit the highest homology suggesting that they are evolutionary the most closely related. Outside their ZFD, GLIS1–3 exhibit little homology with each other or GLI proteins with the exception of an N-terminal, conserved region (NCR) of about 60 aa that GLIS3 has in common with GLI1–3 [9]. …”
Section: Introductionmentioning
confidence: 99%